Functional food product development - Smith, Jim, 1953-; Charter, Edward (Chichester, West Sussex ; Ames, Iowa : Wiley-Blackwell, 2010)
"The market for functional food products is estimated at between US$10 billion and US$30 billion and is expected to double by 2010. With this demand for new products comes a demand for product development and supporting literature for that purpose. This book provides a much-needed review of important opportunities for new products from many perspectives including from those with in-depth knowledge of as-yet unfulfilled health-related needs. The book addresses functional food product development from a number of perspectives: the process itself; idea creation; regulation; health research that may provide opportunities; and processes and ingredients. It also features case studies that illustrate real product development and commercialization histories. Written for food scientists and technologists, the book presents practical information for use in functional food product development. It is intended for use by practitioners in functional food companies and food technology centres and will also be of interest to researchers and students of food science"--Provided by publisher.
Front Matter -- Colour Plates -- New Technologies for Functional Food Manufacture -- Microencapsulation in Functional Food Product Development / Luz Sanguansri, Mary Ann Augustin -- Nanoencapsulation of Food Ingredients in Cyclodextrins: Effect of Water Interactions and Ligand Structure / M.F. Mazzobre, B.E. Elizalde, C. dos Santos, P.A. Ponce Cevallos, M.P. Buera -- Supercritical Carbon Dioxide and Subcritical Water: Complementary Agents in the Processing of Functional Foods / Keerthi Srinivas, Jerry W. King -- Emulsion Delivery Systems for Functional Foods / P. Fustier, A.R. Taherian, H.S. Ramaswamy -- Functional Ingredients -- Functional and Nutraceutical Lipids / Fereidoon Shahidi -- The Use of Functional Plant Ingredients for the Development of Efficacious Functional Foods / Christopher P.F. Marinangeli, Peter J.H. Jones -- Dairy Ingredients in New Functional Food Product Development / S.L. Amaya-Llano, Lech Ozimek -- Probiotics and Prebiotics / Anna Sip, Wlodzimierz Grajek -- The Influence of Food Processing and Home Cooking on the Antioxidant Stability in Foods / Wlodzimierz Grajek, Anna Olejnik -- Development and Commercialization of Microalgae-Based Functional Lipids / Jaouad Fichtali, S.P.J. Namal Senanayake -- Product Design and Regulation -- New Trends for Food Product Design / Juan-Carlos Arboleya, Daniel Lasa, Idoia Olabarrieta, Iñigo Mart̕nez de Marañón -- Reverse Pharmacology for Developing Functional Foods/Herbalc Supplements: Approaches, Framework and Case Studies / Anantha Narayana D.B. -- An Overview of Functional Food Regulation in North America, European Union, Japan and Australia / Paula N. Brown, Michael Chan -- Functional Foods and Health. Functional Foods that Boost the Immune System / Calvin London -- The Mediterranean Diets: Nutrition and Gastronomy / Federico Leighton Puga, Inés Urquiaga -- Functional Foods for the Brain / Ans Eilander, Saskia Osendarp, Jyoti Kumar Tiwari -- Tangible Health Benefits of Phytosterol Functional Foods / Jerzy Zawistowski -- Obesity and Related Disorders / Yanwen Wang -- Omega-3, 6 and 9 Fatty Acids, Inflammation and Neurodegenerative Diseases / Cai Song -- Functional Food in Child Nutrition / Martin Gotteland, Sylvia Cruchet, Oscar Brunser -- Functional Foods and Bone Health: Where are we at? / Wendy E. Ward, Beatrice Lau, Jovana Kaludjerovic, Sandra M. Sacco -- Index -- Food Science and Technology.
Includes bibliographical references and index.
Print version record.
Keywords: Functional foods; Food industry and trade; Food Technology -- methods; Food -- standards; Food-Processing Industry -- methods; Nutritional Physiological Phenomena; HEALTH & FITNESS -- Nutrition; HEALTH & FITNESS -- Diets; MEDICAL -- Nutrition; MEDICAL -- Nursing -- Nutrition; HEALTH & FITNESS -- Food Content Guides; Food industry and trade; Functional foods; Electronic books